Let's solve the problem step by step.
We are given:
- \( B = k - 5k^2 - 1 \)
- \( C = k - 2k^2 \)
We need to find the expression for \( 2B + 3C \).
Step 1: Substitute the expressions for B and C
First, we will substitute the expressions for \( B \) and \( C \) into \( 2B + 3C \).
\[ 2B + 3C = 2(k - 5k^2 - 1) + 3(k - 2k^2) \]
Step 2: Distribute the coefficients
Now, we will distribute the 2 and 3 to the respective expressions:
\[ 2B = 2(k - 5k^2 - 1) = 2k - 10k^2 - 2 \] and \[ 3C = 3(k - 2k^2) = 3k - 6k^2 \]
Step 3: Combine the expressions
Now we will combine \( 2B \) and \( 3C \):
\[ 2B + 3C = (2k - 10k^2 - 2) + (3k - 6k^2) \]
Combine like terms:
\[ = (2k + 3k) + (-10k^2 - 6k^2) - 2 \]
This simplifies to:
\[ = 5k - 16k^2 - 2 \]
Step 4: Write in standard form
In standard form, we typically write polynomials starting with the highest degree term. Therefore, we rearrange it:
\[ = -16k^2 + 5k - 2 \]
Final Result
The expression that equals \( 2B + 3C \) in standard form is:
\[ -16k^2 + 5k - 2 \]